Geometric Quantum Computation with Shortcuts to Adiabaticity. Issue 9 (27th May 2019) - Du, Yanxiong; Liang, Zhentao; Yan, Hui; Zhu, Shiliang
Abstract: Realization of a large‐scale quantum computation relies on fast and high‐fidelity quantum control. Geometric quantum control is thought to be a promising candidate for quantum computation which consolidates the robustness against both random noise (through the global geometrical feature) and systematic errors (through adiabatic characteristic). The adiabatic process of geometric control can be accelerated through an auxiliary Hamiltonian in different scenarios by means of shortcuts to adiabaticity (STA). Especially, the auxiliary Hamiltonian can be absorbed into the original interacting configuration in most of the cases, which allows STA to coalesce with the Abelian or the non‐Abelian geometric control. As a consequence, geometric quantum control can have an enhanced robustness against decoherence after speeding up by STA. Here, the recent theoretical and experimental advances in geometric quantum computation based on STA are reviewed. Abstract : Fast and high‐fidelity quantum control is a key ingredient to realize large‐scale quantum computation. Geometric quantum computation with shortcuts to adiabaticity can consolidate the superiorities of both geometric and adiabatic control, and hence becomes an ideal candidate for quantum computation. Here, the recent theoretical and experimental works in this hot research area are reviewed.